EXPLORING STUDENTS' ACADEMIC HELP SEEKING AND ITS RELATIONSHIP WITH STUDENTS' ACHIEVEMENT - Al Amini Indah Sari; Murni Mahmud; Sahril Nur (Universitas Negeri Manado, 2023)
This study addresses the issue of Help-Seeking Behavior and its Relationship with students’ English Achievement, Help-Seeking Strategies, and Help-Seeking Avoidance with special attention to the point of view of Second-Year Students of MA Madani Alauddin Pao-Pao. Mixed Method was used to carry out this study with the use of Convergent Parallel Design as the design to simultaneously collect both quantitative and qualitative data, and with the support from data collection instrument i.e., Documentation, Questionnaire, and Interview. Three groups of the second-year students were purposively to participate in this study. Fifteen students representing the second-year students as interviewee. Results revealed four things namely: the first, there is a positive relationship between students’ help-seeking behavior and students’ English achievement based on the questionnaire results. The second, there is no significant correlation between students’ academic help-seeking behavior and students’ English achievement with the results of SEM Analysis which all of the p-values were > 0.05. The third, there are 3 strategies used, formal help-seeking; informal help-seeking; and doing instrumental actions. The fourth, there are many reasons of students to avoid seeking help including laziness, low self-esteem, anxiety, uncomfortable feeling, and help-providers’ attitude. This study results showed that help-seeking continue to be an important self-regulatory skill. The researcher believes that these findings could have a profound impact on the way of Help-Seeking is used and viewed. Therefore, English teachers should provide more opportunities to learn this skill to enable students apply it in their academic difficulties.